(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3jhSa Hf YKeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj nfnqRnd GdaQbGf Ydi YHOg djchf ddYGdejf fPjQG hHYO, aEf CYXe GdYdhe ebOGQG HYO GdGSJNGQI eG Uee Hg YRej Ydi GdTQhY ajeG CQOJg, hGdEJjGf HeG bUOJg, fGhjG Cf CSejg HYO Cf CJeeg (S0(3HCfhGQ GdJfRjd hCSQGQ GdJChjd(S1s
(3BNQgG (B:s
(3penf GrdpLnqfpI nhGdnqfGpS HjGf d GrdnhrShGpS, Ch ddPj Ch eJYdb H ojnhrSphoS Cj jhShS aj UOhQge ef LgI GdpLnqfnI hGdfGS hbjd HjGf ddnqfGpS Ydi Cf GdeQGO Hg eG jYe GdKbdjf, hajg JYSa EdG Cf jQGO Hg GdfGSj cbhdg (B: (3njrhne njrOoY GdnqOGpY aEf fSjGf Mb Gddg JYGdi jYe GdKbdjf Yf GdfHj Uqdi Gddg Ydjg hSde (S0(3ef bQC GdeYhPJjf acCfeG bQC GdcJH GdJj CfRdgG Gddg JHGQc hJYGdi(S1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 110s
(3eYLe GdeDdajf (B2 / 266s
(3cTa GdXfhf (B1 / 186s
(3TPQGJ GdPgH (B5 / 392s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs